IMPLEMENTASI PENGUJIAN LEARNING MANAGEMENT SYSTEM APLIKASI PEMBELAJARAN JARAK JAUH BERBASIS MOODLE DI UNIVERSITAS XYZ - Hakim, Lukman; Lumba, Ester; Danuputri, Chyquitha (ZONAsi: Jurnal Sistem Informasi, 2023)
Increasing learning by innovating internet-based information technology and e-learning, providing convenience in increasing learning flexibly without space and time limits, implementing distance learning that is officially licensed by the government, providing fresh air for universities or institutions in developing Innovative applications using the Moodle LMS are more interactive and customized. Writing this article uses an experimental method by designing a moodle LMS with domain hosting in Informatics study program, implementing Moodle LMS to find out how far the comparison is between blended learning which is currently used at XYZ University, based on test results by distributing questionnaires to informatics students, the average usability value is obtained -average 92.1%.